Cherry laurel (Laurocerasus officinalis Roem.) unshelled kernel: A potential feed additive to improve laying performance, yolk fatty acid profile, and antioxidant capacity in laying hens housed with outdoor access - Esma Barasoğlu; Canan Kop-Bozbay (Ciência e Agrotecnologia)
ABSTRACT Phytogenic products are useful poultry feed additives owing to their beneficial effects on health, laying performance, and product quality. This study aimed to determine the effect of cherry laurel (Laurocerasus officinalis Roem.) unshelled kernel (CLUK) dietary supplementation on the laying performance, egg quality, and yolk fatty acid (FA) and antioxidant contents in laying hens. 400 Lohmann Brown hens, housed with outdoor access, were randomly allocated into four groups. Each group comprised four replicates of 25 hens. Hens in the control group were fed on a basal diet without CLUK (0CK), whereas those in the treatment groups were fed on a basal diet supplemented with CLUK at doses of 2.5 (2.5CK), 5 (5CK), or 10 (10CK) g per kg diet for 12 weeks. The egg weight in the 5CK group was higher than that in the 0CK and 2.5CK groups. The feed conversation rate (FCR) in the 2.5CK and 10CK groups was lower than that in the 0CK group. The yolk heptadecanoic acid content was higher in the 5CK group. The yolk docosahexaenoic acid content was upregulated in the 2.5CK and 10CK groups. The yolk n6/n3 ratio was higher in the 0CK. Principal component analysis plot revealed seven egg yolk FAs. The egg yolk 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging capacity in the 10CK group was higher than that in the 0CK and 2.5CK groups. These findings suggest that CLUK is a potential laying hen feed additive and improves egg weight, FCR, and yolk FA profile, DPPH scavenging potential, and n6/n3 ratio.